Analysis Of Shooting Skills Level In Futsal Games In Gradient Fc Bengkulu City - Lendo Litra Solong; Supriyanto Supriyanto; Tito Parta Wibowo (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the level of futsal shooting skills in Futsal Gradient Fc Athletes in Bengkulu City. This research is quantitative descriptive. The variable in this research is futsal shooting skill. The subjects in this study were futsal athletes Gradient Fc Bengkulu City, totaling 18 players. The method used is a survey and data collection techniques using tests and measurements. In this study, to see shooting skills with shooting test instruments. The results of the study 0 people or (0%) were in the very high category, 8 people were in the high category, 5 people were in the medium category, 5 people were in the low category, 0 people were in the very low category. So overall the skill level of Shooting Futsal at Gradients Fc Bengkulu is in the